TRIADIC FUNCTIONS OF SITUATIONAL CONTEXT OF HATE SPEECHES: A CYBERPRAGMATIC PERSPECTIVE (FUNGSI-FUNGSI TRIADIS KONTEKS SITUASIONAL TUTURAN KEBENCIAN: PERSPEKTIF PRAGMATIK SIBER) - R. Kunjana Rahardi (Metalingua: Jurnal Penelitian Bahasa, 2020)
Abstract The objective of this research is to describe the triadic functions of the situational context in the perspective of cyberpragmatics. The research data include excerpts of natural utterances from social media containing triadic meanings and embedded in the situational contexts. Thus, the digital data sources were taken from the utterances in the social media, especially Twitter and  Instagram. The data were collected by applying the observation method and interview method. The observation method included involved interview and uninvolved interview techniques. The interview methods were face-to-face and indirect interviews and the techniques were prompting, recording, and note-taking. The triadic utterances and their situational contexts were identified, selected, and classified into types of data. Further, the types of data were analyzed. The data analysis was carried out using the identity method, particularly the extralingual identity method. The results of the research show that there are five types of triadicity found in the situational context of the cyberpragmatics. They are the triadic function of situational context: (1) to determine the pragmatic meaning of an utterance, (2) as the background of the pragmatic meaning of an utterance, (3) to emphasize the pragmatic meaning of an utterance, (4) to explain the pragmatic meaning of an utterance, (5) to explicate the pragmatic meaning of an utterance. Abstrak Tujuan dari penelitian ini adalah untuk menggambarkan fungsi ketriadisan konteks situasi dalam perspektif pragmatik siber. Data penelitian ini berupa cuplikan tuturan natural manusia yang mengandung makna triadis di dalamnya dan berbalut konteks situasional di sekelilingnya. Data dikumpulkan dengan menerapkan metode simak dan metode cakap. Metode simak yang diterapkan berjenis libat cakap dan non-libat cakap dengan teknik rekam dan teknik catat. Adapun metode cakap yang diterapkan adalah metode cakap semuka dan metode cakap tansemuka yang disertai dengan teknik pancing dan teknik catat serta teknik rekam. Hasil penelitian menunjukkan lima ketriadisan fungsi konteks situasional dalam pragmatik siber, yakni: (1) Ketriadisan fungsi konteks sebagai penentu makna pragmatik tuturan, (2) Ketriadisan fungsi konteks sebagai pelatar belakang makna pragmatik tuturan, (3) Ketriadisan fungsi konteks sebagai penegas makna pragmatik tuturan, (4) Ketriadisan fungsi konteks sebagai penjelas makna pragmatik tuturan, (5) Ketriadisan fungsi konteks sebagai pemerinci makna pragmatik tuturan. Kata Kunci: function triadicity, situational context, cyberpragmatic perspective